Bio- and lithostratigraphy of lower Pleistocene marine successions in western Emilia (Italy) and their implications for the first occurrence of Arctica islandica in the Mediterranean Sea. Issue 2 (September 2019) - Crippa, Gaia; Azzarone, Michele; Bottini, Cinzia; Crespi, Stefania; Felletti, Fabrizio; Marini, Mattia; Petrizzo, Maria Rose; Scarponi, Daniele; Raffi, Sergio; Raineri, Gianluca
Abstract: The Arda and Stirone marine successions (Italy) represent key sections for the early Pleistocene; they were deposited continuously within a frame of climate change, recording the Calabrian cooling as testified by the occurrence of the "northern guests, " such as the bivalve Arctica islandica . In addition, although the first occurrence of A. islandica in the Mediterranean Sea was used as the main criterion to mark the former Pliocene-Pleistocene boundary, the age of this bioevent was never well constrained. Here, we describe the Stirone depositional environment and constrain for the first time the section age using calcareous nannofossil and foraminifera biostratigraphy. We also correlate the Arda and Stirone sections using complementary biostratigraphic and magnetostratigraphic data. Our results indicate that A. islandica first occurred in both the successions slightly below the top of the CNPL7 biozone (dated at 1.71 Ma). Comparisons with other lower Pleistocene Mediterranean marine successions indicate that the stratigraphically lowest level where A. islandica first occurred in the Mediterranean Sea is in the Arda and Stirone sections; these environments satisfied the ecological requirements for the establishment and the proliferation of the species, which only subsequently (late Calabrian) has been retrieved in southern Italy and other areas of the Mediterranean Sea.